The informed writer : using sources in the disciplines - Bazerman, Charles (Boston : Houghton Mifflin, 1995)
This book is about: Writing about reading; Writing using reading; Reading and writing in the disciplines; ...
Keywords: English language; Academic writing; Rhetoric; College readers; Interdisciplinary approach in education; College readers; English language -- Rhetoric; Academic writing